ALAT PENqERING (P.ENIRIS) Alat Pengering (Peniris) Sistem Vakum pada Gorengan Ceriping Ubi SISTEM VAKUM PADA GORENGAN CERIPING ABSTRACT gets UBI, PENGHEMAT UNTUK INDUSTRI PEMAKAIAN MIN'AX-CONNNC KECIL PEDESAAN - Said, Soeprapto Rachmad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
Thecassavachipindustry"Berkah'",inproducing difficuitiesespeciallyiniastening thechipsastheproducts,oftenthemarketingdelivery.Havingbeenfried,theciqssavachipsaretofirstlybedriedwiihconventional*system 48hoursforserondok thechips'still snack,thentheyaremadein plasticpackages. takenumberofoilwiththemsothattheproduct moldythoughtheyarealreadyinthe packages. formorethan24 hoursandTheproblemisthatcanbeeasilyrancidandIt lsdifficulttomaketheoiiinthechipsoutandeffortstakenmaycost,muchsothatitishardfl',th;,;;ii:;;;il;,rrtryto har"suchanact'Considering problem alltheaspectsrevealecl bymeansofvoucherprogrurrr, chipsfrying.above,theservantswishtosolvethetornakeavakumsystemdrayerforcassavaThemethodusedismakingavacuumsystemdryerwithinthespecification follows:(i)thevacuum systemary.,isa cyliniertuue;,(z)it consistsof'twotubes;(3)thelowertubeis usedtostorethecrrips goi.rgtobedrieiandtheupperonefunctionsasthesucker;(4)thediameter_and thehighof thelowertubeare450mmand750mm,andthatof theupperoneare450mmunJqsomm;(5)-iii,pru."J;rh;;;p"i piayed withi850rpmbymeansofelectricmotor%Hp;(6)theuppertubecanbemovedfor180degreebyusingswitchplaced tobedriedareput intothetube,thenairisgiven t,rb"u funtotherroia"r.Thechips,whicharegoingandabsorbingindonethroughponeofthetipofthetube.Theoilwillbeabsoibedintwoways,bymeansofpressuredifferences andairflowmakingtheojloutofthechips.Theresultsofthispractice hours;(2)theoilsucceeded aretobestanding-p^ut position areasfollows:(r)tiaryserondok to'chase snack,itis required2inone processisibout50to60cc; (3)thesnacksi1thetube;(4)timerequiredro.ur.*gingthesnacks'in isabout20m.inutes;(5)having*oik.dfor2-hours,themachineshouldbestopped;(6)theerectricitv thecapacitv approximately .*"0io.th"zhou*isforutout'iij:g;" of1.5kg; (g)timerequired 45menutes,andthioil gained fordryingubr;lkg dryingthecassavachipsis%hoursisi x0,gKw dryrngprocess.Keywords:rvacuum Iilill'fi:il,:Tffi;i,fl;n systemdryer,cassava oariFakultas e/3 standingriif;tietubewithofthe,rb;;,ilo!'l;for"eachpro."*.is15cc.Thecostfor" *:t..i,7/Kwh: chipsfrying,andserondok reknikrrNY,sebagaiKetuaDrs.Suprapto Rp1g7foreachsnack.